Estimating carbon storage performance of Petunia hybrida and Tagetes patula for developing an optimal planning scheme in urban green spaces (Metropolitan area of Kerman) - Seyyed Shahab addin Tayyebi; Shahindokht Barghjelveh; Mojtaba Soleimani-Sardo (علوم محیطی)
Introduction: Enhanced consumption of fossil fuels has increased the amount of carbon dioxide in the atmosphere, which is one of the most important causes of urban pollution, as well as global warming. The development of plant cultivation and the creation of green spaces is one of the most effective methods for carbon storage. Several studies have been conducted to determine the ability of different plants to reduce carbon contents of the atmosphere, many of which recognized the high efficiency of some plants in carbon storage. The aim of this study was to investigate the ability of Petunia hybrida and Tagetes patula in terms of carbon storage, as two key species in Kerman green space developmental projects. Therefore, the results of the present study can be used for urban green space designing with a focus on carbon storage. Material and methods: In this study, the organic carbon content of the samples was determined by an S-N-H-C element analyzer after collecting, weaning and weighing. Subsequently, after surveying the field and taking into account the traffic nodes, the target areas were identified by measuring the highest rates of pollution in certain regions of the Kerman city. Finally, by assessing the green spaces of Kerman, the urban ecological map was prepared for carbon storage. Results and discussion: The results of this research indicated that the carbon storage ability of Petunia hybrida is more than Tagetes patula. Therefore, we suggest that in the western regions towards the center of Kerman city, which had more traffic nodes, Petunia hybrida should be chosen for the development of green spaces.  Conclusion: Since the components of green spaces have unique roles in urban spaces, assessing and understanding the potential capacity of green spaces are so crucial for designing suitable programs for reducing the environmental problems of urban spaces. This study showed that by understanding the capabilities of components of green spaces, we can decrease some urban challenges. Consequently, the cultivation and development of Petunia hybrida will cause more carbon storage than Tagetes patula. Considering the benefits that these kind of plants provide, they should be considered in green spaces’ developmental plans.